Beall-ing O - Joaquin, Jeremiah Joven (Logic and Logical Philosophy, 2019)
In “A neglected reply to Prior’s dilemma” Beall [2012] presents a Weak Kleene framework where Prior’s dilemma for Hume’s no-ought-fromis thesis fails. It fails in the framework because addition, the inference rule that one of its horns relies on, is invalid. In this paper, we show that a more general result is necessary for the viability of Beall’s proposal –  a result, which implies that Hume’s thesis holds in the proposed framework. We prove this result and thus show that Beall’s proposal is indeed viable.